Guidance for delivering surgical procedures outside operating theatres: scoping review - Osborne-Grinter, M; Cousins, S; Ramirez, J; Price, JR; Lancerotto, L; Gardiner, M; Mouton, R; Hinchliffe, R (Oxford University Press, 2024)
Background: This review aimed to examine in-depth the extent and content of guidance related to the delivery of surgical procedures outside of the operating theatre. Methods: Documents concerning the delivery of surgical procedures in non-operating theatre settings were eligible for inclusion. Guidance documents were identified from three sources: electronic databases (MEDLINE and Embase), professional organization websites and expert knowledge. No time limits were imposed. Endoscopic, interventional radiology/cardiology, dental and obstetric procedures were excluded. Eligible documents were included if specifications on the setting and descriptions of procedures were provided. Study titles, abstracts and full texts were screened for relevance. A standardized data extraction form was developed, focusing on: document type, surgical specialty, rationale for developing the guidance, setting specifications, staffing requirements, patient information and safety; descriptive statistics summarized data where appropriate. Verbatim text extracted was summarized descriptively. Results: Of 375 documents identified, 173 full manuscripts were reviewed and 17 were included in the scoping review, published between 1992 and 2022. Guidance provided by documents was limited. They typically included information about general procedures, setting specifications and equipment that may be required to deliver appropriate procedures in the non-operating theatre setting. There was significant heterogeneity in the terminology used to describe the non-operating theatre setting. Appropriate procedures were commonly minor procedures performed under local or topical anaesthesia. The non-theatre setting was recommended to be of adequate size for all appropriate equipment and personnel, with considerations for lighting, waste disposal, ventilation and emergency equipment. Documents also described appropriate training for staff and requirements for personal protective equipment, surgical record keeping, and occupational health and safety guidelines. Conclusions: This scoping review has demonstrated there is significant heterogeneity in guidance documents concerning the delivery of surgical procedures in the non-theatre setting. Standardization of terminology and definitions is required to help inform stakeholders about the development of non-theatre setting practices.